(untitled) (Global Journal of Human-Social Science, 2019)
Restructuring is a song on the lips of many Nigerians. It has trended for decades and seems to be an inter-generational topical issue in Nigeria. The persistent call for restructuring takes numerous dimensions, but particularly outstanding is in the dimension of politics. It is no surprise though, because the philosophy behind the existence of every state and the control of its resources bothers on politics. Therefore, when there is a damaged cog in the wheel of the politics of the state, it becomes imperative to politically restructure the state. Since this is so, the big question then becomes ’what is the damaged cog in the wheel of the politics of Nigeria that is a necessity for restructuring? What are the challenges of political restructuring in Nigeria? And what is the way forward?’ It is in a bid to fill this gap that this paper attempts to answer the above questions through an analytical study of a number of restructuring opinions. The findings of the study proves that ensuring the peaceful coexistence of Nigerian multiethnic nationalities as one peaceful entity called Nigeria and effecting of rapid and competitive development of the different regions of the country among other factors consists the need for restructuring; while elite interest, fear of ethnic dominations, political idiosyncrasy among others construe the challenges facing political restructuring in Nigeria. This paper recommends re-federalization, value reorientation, institutional re-strengthening, ethnic representation amongst others as the solution to restructuring issues in Nigeria.